La dificultad de medir - Samuel Schmidt Nedvedovich (Nóesis)
Network analysis has popularized because it has facilitated approaching structural relationships which other methods ignored, however, still some methodological problems remain to be solved in the search of more complex explanations, such as the generation of centrality indexes in which connections with weight and attributes. In this article we indicate some of the problems we found in our centrality analysis of the Mexican network of power and the difficulty to generate an index of power.